Integrative review on the non‐invasive management of lower urinary tract symptoms in men following treatments for pelvic malignancies. Issue 10 (20th August 2015) - Faithfull, S.; Lemanska, A.; Aslet, P.; Bhatt, N.; Coe, J.; Drudge‐Coates, L.; Feneley, M.; Glynn‐Jones, R.; Kirby, M.; Langley, S.; McNicholas, T.; Newman, J.; et al.
Summary Aim To develop a non‐invasive management strategy for men with lower urinary tract symptoms (LUTS) after treatment for pelvic cancer, that is suitable for use in a primary healthcare context. Methods PubMed literature searches of LUTS management in this patient group were carried out, together with obtaining a consensus of management strategies from a panel of authors for the management of LUTS from across the UK. Results Data from 41 articles were investigated and collated. Clinical experience was sought from authors where there was no clinical evidence. The findings discussed in this paper confirm that LUTS after the cancer treatment can significantly impair men's quality of life. While many men recover from LUTS spontaneously over time, a significant proportion require long‐term management. Despite the prevalence of LUTS, there is a lack of consensus on best management. This article offers a comprehensive treatment algorithm to manage patients with LUTS following pelvic cancer treatment. Conclusion Based on published research literature and clinical experience, recommendations are proposed for the standardisation of management strategies employed for men with LUTS after the pelvic cancer treatment. In addition to implementing the algorithm, understanding the rationale for the type and timing of LUTS management strategies is crucial for clinicians and patients.